A contribuição da dança educativa nas aulas de educação física com crianças de uma escola pública - Pelissoni, Ana Luísa (2013)
This work aimed to make a reflective approach about the study of the movement, which was based on the methodology of Laban. The main objective was to understand the contribution of dance education in the teaching and learning with elementary school children in a school. Therefore, we sought to know how the child learns body movement from labaniano method, taking the student (a) reflect and realize the execution of movements through the relationship of teaching and learning of dance education. Still had the following objectives: to understand the relevance of dance language in the educational process, analyze the gestures and movements used by learners (as); identify which were the gestures and / or bodily actions performed by students (as) in the teaching and learning dance education; see which body parts are involved in the most active movements; identify the feelings expressed by students (as) through body movements; to opportunity bodily experiences and sensitive aesthetic movement, as well as understand how they gave social relationships among children through dance school. Based on studies of Laban (1978), in the book Dominion of movement and works by other researchers dance, art - education, dance education and aesthetic education, subsidies are provided to answer the questions that are proposed to investigate, apart from educational dance workshops conducted in a school and, later, using the method of observation through the visual data, further analysis of gestures and movements across categories of Laban. Through these approaches, sought to provide aesthetic experiences and sensitive movement bringing a new perspective on human movement from dance education